1982
DOI: 10.1002/cm.970020306
|View full text |Cite
|
Sign up to set email alerts
|

In vitro nucleation of microtubules from microtubule‐organizing center prepared from cellular slime mold

Abstract: Nucleus associated bodies (NABs) were isolated from Dictyostelium discoideum or Dictyostelium mucoroides and their ability to nucleate microtubules in vitro was examined. NABs were localized at the tapered ends of the nuclei and released from lysed cells in complex with the nuclei. Microtubules radiating from the NAB could also be isolated with the complex under microtubule stabilizing conditions. The ultrastructure of the isolated NAB showed it to be composed of a core structure surrounded by an amorphous mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The second central motor kinesin in Dictyostelium, Kif9 (orphan), functions in a nuclear role completely separate from that of Kif6, to form at least part of the linkage between the interphase nucleus and the MTOC. Previous structural studies have described 4-to 5-nm-diameter fibers connecting the centrosome and nuclear envelope, and the tight linkage between these two objects is maintained even in the presence of MT poisons (29,44). Thus, it is unlikely that the MT system comprises the sole physical connection between the nucleus and MTOC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The second central motor kinesin in Dictyostelium, Kif9 (orphan), functions in a nuclear role completely separate from that of Kif6, to form at least part of the linkage between the interphase nucleus and the MTOC. Previous structural studies have described 4-to 5-nm-diameter fibers connecting the centrosome and nuclear envelope, and the tight linkage between these two objects is maintained even in the presence of MT poisons (29,44). Thus, it is unlikely that the MT system comprises the sole physical connection between the nucleus and MTOC.…”
Section: Discussionmentioning
confidence: 97%
“…By electron microscopy (EM), the MTOC of Dictyostelium appears as a cytoplasmic cube-shaped structure surrounded by amorphous dense material (39,44). EM, biochemical analyses, antibody labeling, and live-cell imaging studies have demonstrated that during interphase, the cytoplasmic MTOC is firmly and closely attached to the nucleus (28,29,44,48,49,63). Upon entry into mitosis, the MTOC duplicates during prophase and is brought to or into a fenestration of the nuclear envelope, and then it establishes an intranuclear bipolar spindle for division (39,53,64).…”
mentioning
confidence: 99%
“…which microtubules radiate (Roos, 1975a,b;Kuriyama et al, 1982;Euteneuer et al, 1998). The centrosome resides in the cytoplasm but is linked to the nucleus (Roos, 1975a;Omura & Fukui, 1985).…”
Section: (2) Centrosomal Events During Mitosis In Dictyostelium Discomentioning
confidence: 99%
“…). The acentriolar centrosome of D. discoideum is a cuboid structure which consists of a dense, three‐layered core surrounded by an amorphous corona from which microtubules radiate (Roos, 1975 a , b ; Kuriyama et al , ; Euteneuer et al , ). The centrosome resides in the cytoplasm but is linked to the nucleus (Roos, 1975 a ; Omura & Fukui, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the interphase MTOC in the cellular slime mold, Dictyostelium discoideum is a disc-shaped multilayered core embedded in an electron dense granular material [Roos, 19751. It is located next to the nucleus and can be isolated from cells as a coherent unit with the nucleus [Kuriyama et al, 19821. These nucleus associated bodies (NABs), although structurally distinct from mammalian centrosomes, appear to share the common functional property of initiating microtubule assembly in vitro [Kuriyama et al, 1982;Kuriyama, 19841. This suggests the presence of conserved functional elements among different types of MTOCs.…”
Section: Introductionmentioning
confidence: 99%